CULTURAL VALUES LEXICON IN ENGLISH: A COMPREHENSIVE SURVEY OF KEYWORDS AND IDIOMS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article maps the cultural values lexicon of English—from longstanding abstract nouns (e.g., tradition, heritage, honor) to modern ideals (e.g., diversity, sustainability, human rights)—and illustrates how both single keywords and set phrases encode collective identity, moral norms, and historical change. Employing a secondary‐data review of idiom dictionaries, encyclopedic entries, and image archives, we identify core terms and trace their semantic characteristics, collocations, and usage contexts. We also discuss the role of figurative expressions (e.g., “old school,” “melting pot,” “when in Rome”) in conveying evaluative attitudes. Our findings highlight the dynamic interplay between linguistic form and cultural narrative.